Electrokinetic desalination of a farmhouse applying a proton pump approach. First in situ experience. (20th May 2020) - Feijoo, J.; Ottosen, L.M.; Matyscak, O.; Fort, R.
Highlights: On-site desalination intervention of a brick masonry wall affected mainly by sulphates and nitrates. Electromigration was the desalination technique selected to reduce the anion content. A novel proton pump approach, based on the use of two electrodes at the anode was used. The proton pump allowed the flux of electric current to flow between devices for longer. The proton pump approach allowed reaching high efficiency percentages. Abstract: Salt induced decay is considered as a frequent and serious problem that affects the porous materials used in building constructions once in service. To safeguard the integrity and perdurability of the affected monument, the main strategy is focused on to reduce the salt content, as far as possible, by the application of desalination techniques. Among the desalination techniques, it is worth mentioning the application of electrokinetic techniques due to their high efficiency (i.e. efficacy in a short period of time). The present study shows the possibility of the use of an electrochemical desalination technique, by the use of a proton pump at the anode, to desalinate a brick wall of an ancient royal stable of the 18th century. The brick wall selected for this study was severely affected by salt-induced decay caused by the high concentrations of sulphates, nitrates, and chlorides (in the three cases, the concentrations of each anion exceeded the limits from ÖNOR.M.B. 3355-1 where active salt removal is advised). The results achieved by applying the proton pump were compared with those obtained by using devices with a single electrode in the anode. The results obtained show that the chloride, nitrate, and sulphate concentrations were reduced significantly after 2 months of treatment. The amount extracted by the anode devices with two electrodes (proton pump) was greater than that reached in those devices with only one electrode. This fact is related to the proper work of the proton pump, which allowed maintaining the moisture content in the anode poultices for a longer time, favouring a greater current circulation.